Assessing the trade and transport facilitation performance: a manufacturer's perspective / Mohd. Azlan Abu Bakar - Abu Bakar, Mohd. Azlan (2016)
Practitioners and academics agreed that logistics performance significantly influence the efficiency and effectiveness of firm performance. This is because the differentiation in values that customers receive from logistics activities would create the firm’s competitive advantage. Presently, in the global supply chain network, logistics performance measurements are not only referred to firm performance, but also cover the entire logistics supply chain and trade facilitation. It aims to maximise the efficiency of procedures and control governing the movement of goods across national border. Presently, the Logistics Performance Index (LPI) constructs developed by Arvis et al. (2014) were used to determine the overall performance of Malaysian logistics industry. Additionally, environment-friendly was considered vital due to the fact that minimise the amount of emissions in transport operations (Pazirandeh & Jafari, 2013) as well as productions. Six constructs were assessed by the professionals in manufacturing firms, namely customs efficiency, logistics infrastructure, logistics cost, logistics effectiveness, quality of logistics services and environment-friendly. The assessment was based on 129 usable questionnaires from various industries to assess logistics performance. Further analysis were carried out to determine the effects of the six constructs and logistics performance. The Partial Least Square - Structural Equation Modelling (PLS-SEM) approach was used to identify two main objectives, namely the effect of trade and transport facilitation, and the key constructs from the logistics performance model. The results demonstrate that three key determinant factors i.e. customs efficiency, logistics infrastructure, and competence and quality of logistics services mostly reflect the overall logistics performance in Malaysia. However, logistics cost and environment-friendly were found to have negative effects on logistics performance. Despite these findings, results showed that customs efficiency and logistics infrastructure indirectly affect logistics cost. Thus the results indicated that both custom efficiency and logistics infrastructure have the potential to minimise the logistics cost in Malaysia. This study contributes to the body of knowledge through the establishment of relationship between trade transport facilitation and logistics performance in Malaysia from the manufacturing firms’ perspectives. It also provides insight on a different perspective of logistics performance for Malaysia.